Integration of Remote Sensing and Aerogeophysical Data Applied in the Geological Characterization of the Ipueira-Medrado Segment, Andorinhas/BA - Rebouças, Iago Silva; Hühn, Sérgio Roberto Bacelar; Miranda, Mateus de Paula; Salgueiro, Ana Rita Gonçalves Neves Lopes; Sales, Kleiton Camilo da Paz; Duarte, Cynthia Romariz (Anuário do Instituto de Geociências, 2024)
The segment of the Ipueira-Medrado mines constitutes two of the main chromium mines operated by Companhia Ferro-ligas da Bahia (Ferbasa). The research area is located in the municipality of Andorinhas, in the north center of the state of Bahia, in the Piemonte Norte Do Itapicuru region. Therefore, the main objective of the present work is the use of Remote Sensing and Aerogeophysics data to elaborate the geological map of the study area and highlight new target areas for mineral research. The Digital Image Processing (PDI) stage was carried out in an environment in the ENVI® 5.3 software for the scenes of the optical Alos and radar images, Palsar. The treatment of magnetic and radiometric data was carried out in the environment of the software Oasis Montaj 9.10 by Geosoft®. In the Geographic Information System (GIS) platform of ArcGis 10.7.1®, multisource data was integrated. This integration supported the screening of information from local lithologies and the identification of four lithological units: Sienito Itiúba, Santa Luz Unit, São Bento Unit and Jacurici Valley Complex. In this last unit, a combined analysis between Map Algebra and Fuzzy logic was applied to all input raster data, in order to mark out a zoning of potential areas for the occurrence of mafic-ultramafic rocks. In the end, a good relationship was noted between the results obtained with models that already exist in the bibliography. In view of this, the application of the methodology developed in this research requires more robustness for the local geological knowledge, as it will also help in the development of new mineral research endeavors.